Local Culture and Urban Retrofit: Reflections on Policy and Preferences for Wall and Roof Materials - Cravioto, Jordi; Mosqueda, Augusto (Frontiers in Sustainable Cities, 2021)
Retrofitting strategies aim to reduce environmental footprints promoting the development or upgrade of existing infrastructure. One crucial aspect of successful retrofitting strategies is local culture, which can harmonise or come into conflict with retrofitting initiatives. However, investigations on the influence of local practices, particularly in the global south, are limited and such influence deserves more attention in related literature. This article explores the connection between local culture and retrofitting strategies, focusing on wall and roof material selection in the Metropolitan Valley of Oaxaca in Mexico (ZMVO). We begin with a brief review of the retrofitting initiatives at related governmental levels. Then, through a survey, we analyse the choices and reasons for selecting specific materials for walls and roofs in the ZMVO. We discuss to what extent cultural practices and preferences have been considered or left behind in the strategies and ensuing challenges. The findings confirm important premises. First, tradition and community support were not relevant factors in wall or roof material selection. Material reuse, energy efficiency, and sustainability-related reasons were also not essential to the preferences. Instead, protection (against rain, earthquakes, theft and accidents), hygiene, and aesthetics had a consistently higher priority. We also found that poverty or lack of other options intersects with the use of precarious materials, creating constrained choices. However, the most crucial finding was that choosing less environmentally or culturally compatible materials was strongly connected with deprivation, which had important implications in the selection of materials and retrofitting strategies. The current retrofitting initiatives call for sustainability and efficiency, but the local practices render these efforts insufficient and incoherent. Poverty and informal housing are the main emphases of the local policy. However, the policy focuses on new infrastructure and much less on the existing housing, causing less efficient retrofits. Guidelines for more sustainable material selection have advanced, but regulation and enforcement remain weak. We conclude by discussing all these challenges and providing a set of recommended actions in new initiatives.